2021
DOI: 10.3390/ijerph18063103
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory Flexibility of Sustaining Daily Routines and Mental Health in Adaptation to Financial Strain: A Vignette Approach

Abstract: A vignette approach was adopted to investigate flexibility of sustaining daily routines and whether and how this ability was related to mental health at different levels of financial strain. Three separate studies were conducted with community-dwelling adults (N = 1685) in the USA. In Study 1, we drafted, tested, and modified vignettes with reference to pilot data on the relevance of the scenarios and response options. In Study 2, regulatory flexibility of sustaining daily routines, as calculated in term of co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 84 publications
0
3
0
Order By: Relevance
“…As the Centers for Disease Control and Prevention (CDC; 2019) suggests, these routines can lend a sense of control and act as an anchor during chaotic times. Indeed, new research suggests that daily routines may act as an effective coping mechanism for psychological distress caused by difficult life situations like financial strain (Hou et al, 2021). However, less is known about how newly created routines compare with established routines in their relationship with MIL.…”
Section: Evaluating Advice To Create New Routinesmentioning
confidence: 99%
“…As the Centers for Disease Control and Prevention (CDC; 2019) suggests, these routines can lend a sense of control and act as an anchor during chaotic times. Indeed, new research suggests that daily routines may act as an effective coping mechanism for psychological distress caused by difficult life situations like financial strain (Hou et al, 2021). However, less is known about how newly created routines compare with established routines in their relationship with MIL.…”
Section: Evaluating Advice To Create New Routinesmentioning
confidence: 99%
“…Third, Saunders, Lewis & Thornhill (2009) state that questionnaires could be the most suitable method for examining relationships between variables. In this study, the questionnaire incorporates an experimental vignette design, which is defined as a collection of brief descriptions that can simulate the real world (Hou et al, 2021). Vignette is a valuable method for obtaining the participants' opinions or 'intended behaviour' toward multiple scenarios (Atzmüller & Steiner, 2010, p. 129).…”
Section: Methodsmentioning
confidence: 99%
“…The five items were summed, with higher scores indicating higher life satisfaction (range = 5–20). Previous studies showed that the scale is a reliable and valid measure of subjective well-being among the general population [ 49 ] and has demonstrated high internal consistency (α = 0.90) across studies among Chinese [ 50 ]. Alphas for the scale were 0.86, 0.86, and 0.83, respectively, in the current three administrations.…”
Section: Methodsmentioning
confidence: 99%